Artificial Intelligence in the Cultural Industry: Applications and Challenges - Xingwang Zhan (Innovation in Science and Technology, 2025)
This study provides an in-depth analysis of the applications of Artificial Intelligence (AI) in the cultural industry and the challenges and opportunities it brings. Through literature review, case analysis, and expert interviews, this research reveals the key role of AI technology in content creation, cultural heritage protection, personalized recommendation systems, and market analysis. The study points out that while AI has brought innovation and efficiency to the cultural industry, it also faces technological challenges, ethical and legal issues, market acceptance, and consumer trust. This research proposes a series of strategic recommendations, including strengthening technological innovation, improving copyright protection mechanisms, enhancing market segmentation and consumer insights, adapt to digital transformation with cultivation talents. The results of the study provide valuable insights and guidance for policymakers, cultural industry practitioners, and academic researchers.